Effect of Nitrogen Source on Growth Endophytic Yeast from Salacca edulis Reinw. and Bread Quality Analysis - Nuzulul Zahroh; Ulfah Utami; Nur Kusmiyati (Jurnal Biodjati, 2022)
east biomass is often used in the fermentation of bread dough. Dough fermentation can be maximized by adding a nitrogen source. This study used yeast isolates from salak pondoh (YIS-3, YIS-4, and YIS-7). The purpose of this study was to determine the effect of nitrogen addition on yeast growth and bread quality. This study used an experimental approach. The results of the growth study showed that all isolates treated with 0.05% urea produced higher biomass and cell counts than those treated with control. The highest biomass was produced by YIS-7, which was 3.81 g/300mL, while the highest number of cells was produced by YIS-3, which was 29.02x106 cells/mL. The percentage of proofing results showed that all yeast isolates treated with 0.05% urea needed a longer time to achieve the highest proofing. However, the volume of bread after baking showed better results than those treated with control. The largest volume of bread produced by YIS-3, was 972.14 cm3. The results of the organoleptic test showed that P<5%, which means that all treatments had a significant effect on the taste, aroma, color, and texture of the bread. Overall, the panelists gave good acceptance of the bread fermented by YIS-3 with 0.05% urea treatment. So it can be concluded that the addition of urea with a concentration of 0.05% in YIS-3 gave the best effect on the yeast growth and bread quality.